Research on forced displacement in Suba, Bogotá, 2012 - Restrepo Chavarriaga, Guillermo Leon; Fundación Universitaria Juan N. Corpas (Pontificia Universidad Javeriana - Facultad de Enfermería, 2015)
Introduction: studying the problems of people living in displacement is today a national priority due to the fact that it is topical. Objective: To obtain information in the locality of Suba, Bogotá, about displaced population, which is comprised by people of different ages and gender, representing different ethnic groups and different races. Methodology: The sample selection was made through a non-probability sampling. The sample consisted of 32 families convened by the Foundation Salud, Familia y Comunidad. People in displacement conditions were surveyed in order to know previous and current conditions. Results: The families chosen for this study were supported by the Unit of Attention and Orientation to the displaced population, UAO Suba. Its main feature was to be people living in forced displacement from the province colombiana. Conclusions: always significant proportion of people living in displacement of this study are from the Colombian Pacific, the main cause of displacement, armed conflict; In this study we found that most of the group wants to settle in the capital, due to the circumstances of violence experienced prior to displacement. Utility conditions found in the city and attract their stay, the group that wants to stay, aspiring to improve their overcrowded, and have a better quality of life.